ARTISTIC CREATIONS. ORIGINALITY, INSPIRATION, IMITATION AND ARTIFICIAL INTELLIGENCE - Carmen-Oana MIHĂILĂ (Challenges of the Knowledge Society)
Despite an evolution in the harmonization of intellectual property laws, the current EU framework has not created yet a unitary concept of work, originality or authorship. As far as the originality concept is concerned, an artistic creation always has the mark of its author, and originality is „rarely denied to (...) an artistic creation″ as the fathers of French intellectual property stated. The author must avoid any external source of inspiration in order to create an original work of genius, because originality, born spontaneously, from the „vital root of genius″ means that the imitator must share his crown with the object of his imitation. But the concept has been refined over time, and today originality has been redefined, taking into account the classic imprint of the author's personality as well as his intellectual contribution. In these last few years, with the exponential development of artificial intelligence, Pandora's box of copyright issues has been opened. From a simple tool that helped the artist, it has led to original works created without human involvement. There are plenty of such spectacular examples. But can artistic works, created with AI, benefit from copyright protection? Can they be considered related rights? Do they qualify as co-authored works? It hasn't been very long since „non-traditional″ art creations raised similar questions. Cubism, abstract art, Dadaism, conceptual art or digital art, have triggered similar reactions to those produced today by AI art creations. Even if at this moment we cannot offer concrete solutions to protect creations made only by artificial intelligence, without the human factor taking any credit in the creative stages, we will see what the not too distant future will offer.